PANDANGAN GURU SD TERHADAP PEMBELAJARAN MENDALAM DALAM PROSES BELAJAR DI SD NEGERI PARANGTAMBUNG 1 - Kafka Aurel Nafisa; Nurul Atifah Azzahra Khaerunnisa; Amanda; Anita Candra Dewi (STKIP Subang, 2026)
Century learning demands that students have critical and creative thinking skills and the ability to connect knowledge to real life. Therefore, the deep learning approach has begun to be implemented in the learning process in elementary schools. This study aims to determine teachers' views on deep learning in the learning process at Parangtambung 1 Elementary School. This study used a qualitative approach with a descriptive research type. Data collection techniques were carried out through observation, interviews, and documentation. Data were analyzed using the Miles and Huberman model through the stages of data reduction, data presentation, and conclusion drawing. The results show that teachers view deep learning as learning that emphasizes a comprehensive understanding of concepts, encourages students to think critically, and is able to apply knowledge in everyday life. The implementation of deep learning in schools is still in the adjustment stage because teachers need to adjust learning strategies to the conditions and characteristics of students. Obstacles faced include student readiness, limited time, and the need for repeated explanations to ensure students understand the material well. This research contributes to the development of educational science, particularly related to the implementation of deep learning in elementary schools as an effort to create more meaningful and student-centered learning.